THE EFFECT OF WORKLOAD ON FATIGUE IN NURSES IN THE HOSPITAL OF SURAKARTA IN 2023: THE EFFECT OF WORKLOAD ON FATIGUE IN NURSES IN THE HOSPITAL OF SURAKARTA IN 2023 - Piaster, Elyzabeth Hilda; Mardiyati, Septiana Hanifah; Kartika, Putriani; Hasanah, Ulfah Uswatun; AlMubaroq, Misbakhul Munir (Jurnal Mitra Kesehatan, 2024)
introduction : Workload is a factor that influences nurses' ability to provide healthcare services. The diverse nursing tasks, which involve handling patients with various medical conditions and varying levels of dependency, can create a significant burden for nurses. Excessive workload can lead to fatigue, which in turn can reduce performance and increase the risk of errors in work. This study uses a quantitative approach with a cross-sectional design. The sample consists of all the nurses working in the InpatientWard of Surakarta General Hospital, totaling 95 individuals, representing the entire population. Results : The results of the statistical analysis using the Chi-Square test indicate an Asymp Sig value of 0.695, which is greater than 0.05. This suggests that there is no significant relationship between the level of education and the level of nurse fatigue. In other words, differences in education level do not affect the level of fatigue experienced by nurses, based on the statistical tests conducted..